Use of Kirkpatrick’s model for evaluation of reaction and learning of participant of national level workshop on linear regression - Chatterjee, Kunal; Yadav, Arun Kumar; N., Ananad; Malik, Awadesh; Kotwal, Atul; Kunte, Renuka (International Journal Of Community Medicine And Public Health, 2018)
Background: Workshop is a very useful learning method for increasing the understanding and knowledge of participant. We conducted a workshop and evaluated it using Kirpatrick's model for evaluation. Methods: A national level workshop was conducted for MBBS and MD students. Feedback about the reaction of the participant was taken at the end of the participant and also a pre-test and post-test assessment was done. Results: Out of total 28 participants 19 (67.9%) were females and 9 (32.1%) were males. All (100%) attendee said that they liked, enjoyed and considered the training relevant. For learning evaluation the pretest score and posttest score were taken. The average pretest score was 4.1 (SD=2.1). The average posttest score was 6.5 (SD=2.1). The difference was statistically significant (p=0.0002). On question of rating of overall conduct of the workshop 11 (39.3%) rated the workshop excellent, 13 (46.4%) good and 4 (14.29%) did not answer the question. On asking the question on the topic on future workshop they would like to be conducted 16 (57.1%) said multiple linear regression, 12 (42.3%) each on logistic regression and met-analysis, 09 (32.1%) on cox proportional hazard ratio, 3 (10.7%) on SPSS, and 01 (3.5%) on infectious disease modeling. Conclusions: Evaluation of workshop is important for continuing improvement of teaching learning process. Participant positive feedback and objective evidence of improvement in learning proves effectiveness of the workshop. Kirpatrick’s offers a model for various stages of learning process and can be used for assessment of workshops.